2001
DOI: 10.1002/1097-0215(200002)9999:9999<::aid-ijc1038>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Local immunotherapy of glioma patients with a combination of 2 bispecific antibody fragments and resting autologous lymphocytes: Evidence for in situ T‐cell activation and therapeutic efficacy

Abstract: After adoptive transfer of pre‐activated lymphocytes into the operation cavity of glioma patients, tumor regression and improved survival have been reported in some patients. Results were most impressive when bispecific antibodies with tumor × CD3 specificity were also applied. In this study, we attempted to avoid time‐consuming pre‐activation procedures for adoptively transferred cells by using a combination of bispecific antibodies directed to the EGF receptor (EGFR) on tumor cells and to CD3 and CD28 on T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…Clinical trials of adoptive immunotherapy of GBM with human T lymphocytes were based on either intravascular or intracavitary administrations. [34][35][36] However, the survival and activity of T cells within the cerebro-spinal fluid remains unclear as no studies have been performed to describe their behavior or their ability to move and infiltrate the brain parenchyma. Our approach is based on the direct injection of allogeneic amplified gd T cells in the parenchyma, all around the resection cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of adoptive immunotherapy of GBM with human T lymphocytes were based on either intravascular or intracavitary administrations. [34][35][36] However, the survival and activity of T cells within the cerebro-spinal fluid remains unclear as no studies have been performed to describe their behavior or their ability to move and infiltrate the brain parenchyma. Our approach is based on the direct injection of allogeneic amplified gd T cells in the parenchyma, all around the resection cavity.…”
Section: Discussionmentioning
confidence: 99%
“…BiAbs created to redirect CD3-, CD16-, or CD64-positive effector cells to numerous tumor-associated antigens (25 -40), including EGFR (41,42), have shown promising antitumor effects in both preclinical and clinical studies (reviewed in ref. 18).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor regressions and prolonged survival in the majority of patients were reported in a study where lymphokine-activated killer cells preloaded with chemically cross-linked bsAbs with anti-glioma activity (but unknown specificity) were locally applied with Ommaya reservoirs (30). Also, resting T cells preloaded with chemically prepared EGFR-specific T-cell-recruiting antibody fragments were applied in a similar way and evidence for clinical activity was observed in some patients (31). We have observed that T-cell-recruiting bsAbs are rapidly internalized after binding to T cells, which would adversely affect the efficacy of T cells preloaded with bsAbs.…”
Section: Ac133âcd3 Bsab Does Not Affect Hscs At Concentrations Effectmentioning
confidence: 93%